2018
DOI: 10.1016/j.ebiom.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Micrornas Predict Survival of Patients with Tumors of Glial Origin

Abstract: The World Health Organization has recently introduced molecular prognostic-diagnostic biomarkers in the classification of Central Nervous System (CNS) tumors. In order to characterize subclasses of tumors that cannot find a precise location in the current classification, and, or cannot be tested because of scant material, it is important to find new molecular biomarkers in tissue and, or biological fluid samples. In this study, we identified serum microRNAs that could serve as biomarkers for the diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Downregulated hsa-miR-4443 in ovarian cancer contributes to metastasis and tumorigenesis ( 27 ). However, several studies revealed that hsa-miR-4443 is up-regulated in diseases such as acute ischemic stroke ( 28 ), central nervous system tumors ( 29 ), and drug-resistant non-small cell lung cancer ( 30 ), which leads to pathogenic processes. hsa-miR-4443 is detected in different samples, such as tissues, serum, monocytes, or exosomes, thereby leading to no comparability of hsa-miR-4443 expression among different diseases ( 27 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulated hsa-miR-4443 in ovarian cancer contributes to metastasis and tumorigenesis ( 27 ). However, several studies revealed that hsa-miR-4443 is up-regulated in diseases such as acute ischemic stroke ( 28 ), central nervous system tumors ( 29 ), and drug-resistant non-small cell lung cancer ( 30 ), which leads to pathogenic processes. hsa-miR-4443 is detected in different samples, such as tissues, serum, monocytes, or exosomes, thereby leading to no comparability of hsa-miR-4443 expression among different diseases ( 27 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating miRNAs are being widely studied as potential biomarkers of diagnosis and prognosis in different diseases due to their stability and the ease to be measured in tissues and biological fluids [26]. Most of these studies are related to cancer research and have demonstrated the ability of circulating miRNAs as a new and reliable diagnosis and prognosis biomarker to detect and identify different cancer [2729]. Recent studies elucidate the role of miRNAs in neurodegenerative diseases, such as MS, and their capacity to predict disease subtype with a high degree of accuracy [30, 31], as well as, response to a specific treatment [32].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this notion, the miR-4443 locus is frequently deleted in cancers based on TCGA data; and a tumor suppressor role for miR-4443 was also reported in other cancer types, i.e., osteosarcoma [2], hepatocellular carcinoma [3], ovarian cancer [4], and glioblastoma [5]. On the other hand, miR-4443 was shown to promote the resistance of non-small cell lung cancer cells, as well as metastatic breast cancer cells, to the chemotherapeutic agent epirubicin [6,7]; and its elevated levels in plasma were suggested as a biomarker of glial tumors [8]. In addition to its function in cancer cells, miR-4443 was reported to regulate the behavior of immune cells, i.e., CD4+ T cells in the context of Graves' Disease [9] as well as mast cells, notably via microvesicles secreted from T cells [10].…”
Section: Introductionmentioning
confidence: 91%